Influence of UV/Ozone Treatment on Threshold Voltage Modulation in Sol–Gel IGZO Thin-Film Transistors - Kim, Wonsik; Lee, Won June; Kwak, Taehyun; Baek, Seokhyeon; Lee, Seung Hoon; Park, Sungjun (Advanced Materials Interfaces, 2022)
Sol–gel indium–gallium–zinc oxide (IGZO) semiconductors are developed as active components of thin-film transistors (TFTs) because of their high electron mobility, cost-effective large-area fabrication, and applicability for flexible substrates. Controlling oxygen vacancies (Vo) in the IGZO semiconductor channel is always problematic for reliable and long-term operation. Surplus interfacial charges inside the IGZO channel cause negative shifts in threshold voltages (Vth), resulting in depletion-mode operation and involuntary high current output. The room temperature and rapid (<3 min) modulation of Vth using a novel ultraviolet ozone (UVO) treatment of IGZO layer (In:Ga:Zn = 7:1:2) are reported. Physicochemical and electrical analysis reveals that UVO treatment enables the reduction of Vo and increases M-O bonding with invariant contact resistance, resulting in the normalization of Vth close to 0 V and high operational durability under long-term bias stress. As a proof of concept, this study demonstrates the depletion-load n-type inverters comprising depletion and enhancement modes (without & with UVO) on the same substrate that allow high gain (≈10) with a moderate noise margin. This UVO treatment of the active layer is advantageous for the effective modulation of Vth with stable operation under long-term bias stress and is superior to logic inverters based on single-mode sol–gel oxide transistors.
Keywords: Bias stress; C. thin film transistor (TFT); Inverter; Sol'gel; Solution-processed; Solution-processed thin-film transistor; Threshold voltage modulations; Ultraviolet-ozone treatment; UV-ozone treatment; V th modulation; indium–gallium–zinc oxide; inverters; oxygen vacancy; solution-processed thin-film transistors; ultraviolet ozone treatment; V th modulation